2015
DOI: 10.1001/jamadermatol.2014.2098
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Eczema and Increased Fracture and Bone or Joint Injury in Adults

Abstract: The results of this study suggest that eczema in adulthood is a previously unrecognized risk factor for fracture and other injury causing limitation. Future studies are needed to confirm these associations. The findings may warrant the development of preventive measures for injury risk reduction in adult patients with eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 49 publications
0
38
0
2
Order By: Relevance
“…Understanding the epidemiology of atopic dermatitis (AD or eczema) is essential for identifying at‐risk populations and potentially modifiable risk factors, and ultimately in developing interventions that could prevent eczema in the general population. Much of our knowledge of the epidemiology of eczema in the U.S.A. comes from a number of US population‐based studies, which analysed data from the National Survey of Children's Health (NSCH), National Health Interview Survey (NHIS) and National Health and Nutrition Examination Survey (NHANES) . These studies employed different approaches to identifying eczema, including caregiver‐ and self‐reported diagnosis of eczema ever (NHANES) or in the past year (NSCH and NHIS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the epidemiology of atopic dermatitis (AD or eczema) is essential for identifying at‐risk populations and potentially modifiable risk factors, and ultimately in developing interventions that could prevent eczema in the general population. Much of our knowledge of the epidemiology of eczema in the U.S.A. comes from a number of US population‐based studies, which analysed data from the National Survey of Children's Health (NSCH), National Health Interview Survey (NHIS) and National Health and Nutrition Examination Survey (NHANES) . These studies employed different approaches to identifying eczema, including caregiver‐ and self‐reported diagnosis of eczema ever (NHANES) or in the past year (NSCH and NHIS).…”
mentioning
confidence: 99%
“…Much of our knowledge of the epidemiology of eczema in the U.S.A. comes from a number of US populationbased studies, which analysed data from the National Survey of Children's Health (NSCH), National Health Interview Survey (NHIS) and National Health and Nutrition Examination Survey (NHANES). [1][2][3][4][5][6][7][8][9][10][11][12] These studies employed different approaches to identifying eczema, including caregiver-and self-reported diagnosis of eczema ever (NHANES) or in the past year (NSCH and NHIS). While previous studies validated different questionnaires for self-and caregiver-reported eczema, 13,14 the validity of the particular questions employed by NSCH, NHIS and NHANES has not previously been investigated.…”
mentioning
confidence: 99%
“…[1][2][3] Adults with moderate-to-severe AD have been shown to have poorer health status, 1 sleep disturbances, 1 higher rates of fractures and other injuries, 4 obesity and other cardiovascular disease risk factors, 5,6 and depression and other mental health comorbidities. 7 The mainstays of treatment for AD are emol-lients, topical corticosteroids, calcineurin inhibitors and avoidance of exacerbants.…”
Section: Original Article P 1621mentioning
confidence: 99%
“…For example, taurolidine 2% was shown to be active against Aspergillus fumigatus isolates and used for pleural decontamination during surgery for chronic pulmonary aspergillosis. 4 However, although the newer generation of surgical antiseptics is much safer, hydrogen peroxide has recently been attributed to causing a massive gas embolism during surgery. 5 Understanding the clinical significance of antiseptics in mycetoma management will determine potential for this previously unexplored therapeutic avenue to be formalized.…”
Section: Original Article P 1657mentioning
confidence: 99%
“…A study of 27,556 children aged 0–5 yrs from the National Survey of Children's Health found that children with AD and/or allergic disease had higher odds of serious injury requiring medical attention, which was partially mediated by psychologic and behavioral disorders . Similarly, a study 27,556 adults from the National Health Interview Survey found that adults with eczema had higher odds of fractures, bone and joint injuries, particularly in those with sleep disturbances and psychologic and behavioral disorders . These studies suggest that patients with AD may have decreased BMD, thereby predisposing to increased fractures.…”
mentioning
confidence: 99%